Rapid microevolution of biofilm cells in response to antibiotics - Penesyan, Anahit (2020)
Infections caused by Acinetobacter baumannii are increasingly antibiotic resistant, generating a significant public health problem. Like many bacteria, A. baumannii adopts a biofilm lifestyle that enhances its antibiotic resistance and environmental resilience. Biofilms represent the predominant mode of microbial life, but research into antibiotic resistance has mainly focused on planktonic cells. We investigated the dynamics of A. baumannii biofilms in the presence of antibiotics. A 3-day exposure of A. baumannii biofilms to sub-inhibitory concentrations of antibiotics had a profound effect, increasing biofilm formation and antibiotic resistance in the majority of biofilm dispersal isolates. Cells dispersing from biofilms were genome sequenced to identify mutations accumulating in their genomes, and network analysis linked these mutations to their phenotypes. Transcriptomics of biofilms confirmed the network analysis results, revealing novel gene functions of relevance to both resistance and biofilm formation. This approach is a rapid and objective tool for investigating resistance dynamics of biofilms.